Thermomechanical coupled waves in a viscoplastic medium (Archives of Mechanics - Test, 2002)
Ideas of Perzyna's theory of material systems in the cases of viscoplastic materials and heat conductors are elaborated. Both theories are based on the notion of a method of preparation. They are combined into one coupled model for an elasto-viscoplastic heat conductor. We study its behavior by numerically calculating solutions for plane waves passing through a body.